Beginning reactive programming with Swift : using RxSwift, Amazon Web Services, and JSON with iOS and macOS - Feiler, Jesse (Apress, 2018)
Learn the basics of reactive programming and how it makes apps more responsive. This book shows you how to incorporate reactive programming into existing development products and cycles using RXSwift and RXCocoa on iOS and Mac. As we move away from the traditional paradigm of typing or touching one step at a time to interact with programs, users expect apps to adapt and not need constant hand-holding. People today expect their devices to do much more than just follow commands. They expect devices to react and adapt. Reactive programming, a new term for asynchronous processing, requires new app architectures, and you'll learn how these are already built into iOS and macOS in many places. As part of this more complex environment, you'll move beyond Cocoa and Cocoa Touch to incorporate data from Amazon Web Services (AWS), JavaScript Object Notation (JSON), and other formats, and standards. Together with the concepts of reactive programming and RxSwift, these tools help you build more powerful and useful apps that have wide appeal and use. What You'll Learn Work with tools such as Darwin microkernel, RxSwift, and RxCocoa Use Git repositiories and other resoucrces to get into coding Create apps that adapt to gestures and UI interaction as well as what's happening in and around the environment of the app itself. Who This Book Is For This book is for Swift programmers interested in learning to create reactive apps with RxSwift.